Cytology of Pericardial Effusion due to Malignancy - Kalogeraki Alexandra; Lazopoulos George; Papadakis Georgios Z.; Tamiolakis Dimitrios; Karvela-Kalogeraki Iliana; Karvelas-Kalogerakis Mihailos; Segredakis John; Papadakis Michael; Moustou Eleni; Datseri Galateia; Chalkiadakis George E.; Tzardi Maria (Romanian Journal of Internal Medicine, 2016)
Background. Malignant pericardial effusion occurs in one tenth of all cancers. It is a very serious disorder that is mainly a secondary process due to metastasis because primary neoplasms of the pericardium such as mesotheliomas, sarcomas being exceedingly rare.